Real-time quantitative monitoring of cerebral blood flow by laser speckle contrast imaging after cardiac arrest with targeted temperature management. Issue 6 (June 2019) - He, Junyun; Lu, Hongyang; Young, Leanne; Deng, Ruoxian; Callow, Daniel; Tong, Shanbao; Jia, Xiaofeng
Brain injury is the main cause of mortality and morbidity after cardiac arrest (CA). Changes in cerebral blood flow (CBF) after reperfusion are associated with brain injury and recovery. To characterize the relative CBF (rCBF) after CA, 14 rats underwent 7 min asphyxia-CA and were randomly treated with 6 h post-resuscitation normothermic (36.5–37.5℃) or hypothermic- (32–34℃) targeted temperature management (TTM) (N = 7). rCBF was monitored by a laser speckle contrast imaging (LSCI) technique. Brain recovery was evaluated by neurologic deficit score (NDS) and quantitative EEG – information quantity (qEEG-IQ). There were regional differences in rCBF among veins of distinct cerebral areas and heterogeneous responses among the three components of the vascular system. Hypothermia immediately following return of spontaneous circulation led to a longer hyperemia duration (19.7 ± 1.8 vs. 12.7 ± 0.8 min, p  < 0.01), a lower rCBF (0.73 ± 0.01 vs. 0.79 ± 0.01; p  < 0.001) at the hypoperfusion phase, a better NDS (median [25th–75th], 74 [61–77] vs. 49 [40–77], p  < 0.01), and a higher qEEG-IQ (0.94 ± 0.02 vs. 0.77 ± 0.02, p  < 0.001) compared with normothermic TTM. High resolution LSCI technique demonstrated hypothermic TTM extends hyperemia duration, delays onset of hypoperfusion phase and lowered rCBF, which is associated with early restoration of electrophysiological recovery and improved functional outcome after CA.